Recent New Drug Approvals, Part 2: Drugs Undergoing Active Clinical Studies in Children - Chhim, Rebecca F. (Pediatric Pharmacy Advocacy Group, 2013)
The objective of this 2-part review is to provide information about drugs that have been recently approved by the US Food and Drug Administration. Part 1 reviewed recently approved drugs with pediatric indications. Part 2 reviews drugs recently approved only in adults and have published or ongoing studies in children.